2006
DOI: 10.1038/nprot.2006.430
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ready-to-use, storable and reconstituted type I collagen from rat tail tendon for tissue engineering applications

Abstract: Collagen is a widely investigated extracellular matrix material with extensive potentials in the field of tissue engineering. This protocol describes a method to prepare reconstituted collagen that can be ready-to-use, storable and suitable for further in vitro and in vivo investigations. Type I collagen was extracted from rat tail tendons and processed in acetic acid solution to obtain sterile soluble collagen. At first, crude collagen was dissolved in acetic acid, then frozen at -20 degrees C and lyophilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
361
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 480 publications
(366 citation statements)
references
References 16 publications
0
361
0
5
Order By: Relevance
“…Collagen was obtained from RTT and solubilized at 4 mg/mL in 0.02 M acetic acid according to a previously developed protocol [10]. Collagen gels were prepared on ice at two different pHs, with seven different salt concentrations corresponding to different ionic strengths, and gelled at three different temperatures.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Collagen was obtained from RTT and solubilized at 4 mg/mL in 0.02 M acetic acid according to a previously developed protocol [10]. Collagen gels were prepared on ice at two different pHs, with seven different salt concentrations corresponding to different ionic strengths, and gelled at three different temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2. Results from the turbidity measurements as a function of pH (7,10), ionic strength (c1, c2, c3, c4, c5, c6, c7) and temperature (T1 = 4 °C, T1* = 4 °C and 21 °C after 38 days, T2 = 21 °C, T3 = 37 °C): Final absorbance for all the types of gels and t 1/2 for gels prepared at pH 10. The kinetics of gels prepared at pH 7 as a function of collagen concentration, temperature and ionic strength has already been widely discussed by several authors [23,24,30,31].…”
Section: Turbidity Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, an understanding of the structure of the whole collagen protein is still required [Orgel, et al, 2001]. However, this task is always hampered by the low quality of the collagen derived from conventional procedures, including neutral salt and acetic acid-extraction [Becker, & Timpl, 1972;Miller, et al, 1982;Chandrakasan, et al, 1976;Rajan, et al, 2007] (A comparison of the three procedures is shown in Fig. 1).…”
Section: Experimental Studies Using Synthetic Peptidesmentioning
confidence: 99%